Narratives without paragraph breaks by Bernardo Carvalho, João Gilberto Noll and Samuel Rawet - Jaime Ginzburg (Matraga, 2018)
In “Ciúmes”, a short story written by Bernardo Carvalho, the main character is a powerful and authoritarian man who’s dealing with organized crime. One importante aspect in the short story is that there are not paragraph breaks, as if the narrative should be exposed and understood at once, without interruption, as a singular and continuous flow. In order to understand that, we discuss this formal resource and compare “Ciúmes” to other texts written by Samuel Rawet and João Gilberto Noll.